Kantei diplomacy? Japan's hybrid leadership in foreign and security policy. Issue 2 (4th March 2017) - Pugliese, Giulio
ABSTRACT: This article operationalizes Japanese leadership in foreign and security policy, specifically the Abe administrations' consistent China balancing. It will do so to dispel instances of Premier-centered diplomacy and posit that Abe's diplomatic agenda has rested on a 'hybrid' policy-making authority, where the leverage enjoyed by the Prime Minister's office (the Kantei) rested on little-appreciated politicized personnel appointments and demotions within the bureaucratic apparatus, specifically the Ministry of Foreign Affairs. Moreover, successful Japanese leadership has functioned especially when operating within the scope of the US strategic framework towards East Asia. While structural constraints, such as the ever-present influence of the USA and bureaucratic coordination, may constrain options, effective leadership in foreign policy-making can indeed make a difference within those boundaries.